2016
DOI: 10.4142/jvs.2016.17.1.97
|View full text |Cite
|
Sign up to set email alerts
|

Expression of neurotrophic factors in injured spinal cord after transplantation of human-umbilical cord blood stem cells in rats

Abstract: We induced percutaneous spinal cord injuries (SCI) using a balloon catheter in 45 rats and transplanted human umbilical cord blood derived mesenchymal stem cells (hUCB-MSCs) at the injury site. Locomotor function was significantly improved in hUCB-MSCs transplanted groups. Quantitative ELISA of extract from entire injured spinal cord showed increased expression of brain-derived neurotrophic factor (BDNF), nerve growth factor (NGF) and neurotrophin-3 (NT-3). Our results show that treatment of SCI with hUCB-MSCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…Regarding the mechanisms underlying PA, we demonstrated that A91 immunization induces a specific anti-A91 response that is capable of producing—in vitro—brain derived neurotrophic factor (BDNF), a molecule that induces axonal regeneration and confers motor function improvement after SC-injury. Some studies have also shown that BDNF and another neurotrophic factor, NT-3, prevent neuronal apoptosis [ 26 , 27 ] and promote axonal sprouting and regeneration [ 28 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the mechanisms underlying PA, we demonstrated that A91 immunization induces a specific anti-A91 response that is capable of producing—in vitro—brain derived neurotrophic factor (BDNF), a molecule that induces axonal regeneration and confers motor function improvement after SC-injury. Some studies have also shown that BDNF and another neurotrophic factor, NT-3, prevent neuronal apoptosis [ 26 , 27 ] and promote axonal sprouting and regeneration [ 28 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the selection of UCB-MNCs, the aim is to improve recovery after chronic SCI. Several mechanisms have been proposed for the UCB-MNCs to improve recovery after CNS injury, involving secretion of anti-inflammatory cytokines [ 24 , 25 , 26 ], growth factors release [ 27 , 28 , 29 ], matrix metalloproteinase upregulation [ 25 ], tissue plasminogen activator downregulation [ 26 ], apoptosis prevention [ 24 ], mediation in myelination process [ 30 , 31 ], decreased gliosis [ 32 ], and increased angiogenesis [ 33 ].…”
Section: Cell Therapiesmentioning
confidence: 99%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ nerve growth factor (NGF) in the injured spinal cord is the main therapeutic mechanism of this effect 14 . Most studies of stem cell therapy in SCI have focused on motor limb functions and sensory recovery.…”
mentioning
confidence: 99%